Incubadora e startup: estudo bibliométrico dos últimos 10 anos no Brasil e no mundo - Ferreira, Eva Vilma Costa (Universidade Federal do Tocantins, 2021)
The present work focuses on a bibliometric study on incubators and Startup’s in Brazil and in the world over the last decade, with the purpose of analyzing new research related to the theme with a focus on innovative proposals that contribute to the development of enterprises and conduct a bibliometric study of the literature related to the Business Incubator and Startup published in the last ten years in Brazil and in the world, through the Spell and Scopus database. After a cluster of data and an analysis of the importance of the publications made, Brazil has been encouraging research in the area, and promising the space gained in the last decade by researchers in a national and international scenario as well.